2005
DOI: 10.1111/j.1469-8137.2005.01477.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between phenology and the remobilization of nitrogen, phosphorus and potassium in branches of eight Mediterranean evergreens

Abstract: Summary• Few studies have examined the effects of plant growth on nutrient remobilization in phenologically contrasting species. Here we evaluated the consequences of above-ground seasonality of growth and leaf shedding on the remobilization of nutrients from branches in eight evergreen Mediterranean phanaerophytes that differ widely in phenology.• Vegetative growth, flower bud formation, flowering, fruiting, leaf shedding, and the variations in nitrogen (N), phosphorus (P) and potassium (K) pools in branches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 59 publications
4
57
1
2
Order By: Relevance
“…However, since age-related trends in both leaf N and P have been reported only rarely, it is unclear whether this is a general phenomenon or one peculiar to the species we studied. While similar age-related trends in leaf P and N have been observed in several tree species (Chapin and Kedrowski 1983;Nambiar and Fife 1991;Mediavilla and Escudero 2003a;Niinemets et al 2004;Milla et al 2005), in other species N and P have shown rather different time trends (Hevia et al 1999).…”
Section: Partial Uncoupling Of Age-related Trends In Leaf N and Psupporting
confidence: 69%
“…However, since age-related trends in both leaf N and P have been reported only rarely, it is unclear whether this is a general phenomenon or one peculiar to the species we studied. While similar age-related trends in leaf P and N have been observed in several tree species (Chapin and Kedrowski 1983;Nambiar and Fife 1991;Mediavilla and Escudero 2003a;Niinemets et al 2004;Milla et al 2005), in other species N and P have shown rather different time trends (Hevia et al 1999).…”
Section: Partial Uncoupling Of Age-related Trends In Leaf N and Psupporting
confidence: 69%
“…Tomlinson et al (2013), while comparing leaf traits of different plant species growing in wet and arid environments, observed that leaves of species adapted to arid sites are small with high K concentrations. Furthermore, it was observed that tree species at the driest sites, such as in mediterranean evergreen and dry tropical forests, have a higher capacity to change their seasonal internal allocation of K, with a higher allocation of K to leaves during summer (the driest season) than the species at wetter sites (Milla et al, 2005;Rivas-Ubach et al, 2012;Sardans et al, 2012a).…”
Section: K Stoichiometry and Water Availability In Terrestrial Ecosysmentioning
confidence: 99%
“…As observed in plants adapted to severe periods of drought, P tends to remobilize from leaves to roots, whereas K has the opposite movement, as observed in Mediterranean trees during summer drought (Milla et al, 2005;SanzPérez et al, 2009;. Plants with the genotypic capacity to maintain N, P, and K concentrations and contents under drought have a competitive advantage if drought persists or becomes more severe (Ghandilyan et al, 2009).…”
Section: Drought Shifts In Elemental Compositionmentioning
confidence: 99%
“…In addition to activating mechanisms for improving the capacity to take up water, plants respond to drought by enhancing mechanisms for conserving water and nutrients, such as the retranslocation of nutrients prior to tissue senescence (Heckathorn andDeLucia, 1994, 1996;Correia and Martins-Loução, 1997;Milla et al, 2005) and the internal remobilization of nutrients dependent on the availability of water . As observed in plants adapted to severe periods of drought, P tends to remobilize from leaves to roots, whereas K has the opposite movement, as observed in Mediterranean trees during summer drought (Milla et al, 2005;SanzPérez et al, 2009;.…”
Section: Drought Shifts In Elemental Compositionmentioning
confidence: 99%